Answer:
<em>a) 15 b) 6 c) -3</em>
Step-by-step explanation:
x - y = 3
a) 5 (x - y) = 5 (3) = 15
b) 2x - 2y = 2 (x - y) = 2 (3) = 6
c) y - x = -1 (x - y) = -1 (3) = -3
Answer: i think a
Pentagon
Step-by-step explanation:
if not im super sorry
I am sure that This one would be c
Answer:
2
Step-by-step explanation:
A = P( 1+r/n) ^ (nt)
P is the amount invested
r is the rate
n is the number of times per year the interest is compounded
t is the number of years
every 6 months is twice a year
so n is 2
1. (2x + 1)(x - 7)
2. -x - 4
3. -31x -35
4. 57x + 112
5. (-x) (-x)